Contemplating the Impact of the Moderators Agency Cost and Number of Supervisors on Corporate Sustainability Under the Aegis of a Cognitive CEO - Sarfraz, Muddassar; Ozturk, Ilknur; Shah, Syed Ghulam Meran; Maqbool, Adnan (Frontiers in Psychology, 2020)
The social cognitive theory emphasizes the risk-taking behaviour of an entrepreneur which leads him to take the right decision. In this regards, cognitive CEO has been formulated through DAE statistical technique. Specifically, CEO attributes such as CEO age, CEO compensation, CEO tenure, goodwill and CEO attended the number of meetings has been endorsed for input while influencing the intangible assets as an output. Chinese SMEs have been selected for the empirical analysis for the years 2014-2018. The empirical results have revealed that cognitive CEO augments corporate sustainability while agency cost and the number of supervisors have deterred the corporate sustainability vehemently. Meanwhile, earnings per shares and high total assets variables are vehicles for maintaining the firms’ sustainable growth. Additionally, it has been recommended that firms having loan burden cannot maintain sustainable corporate growth. Lastly, the execution of 2SLS instrumental regression authenticates the veracity of the results.